1978
DOI: 10.1111/j.1096-3642.1978.tb01075.x
|View full text |Cite
|
Sign up to set email alerts
|

The ecology and evolution of male reproductive behaviour in the bees and wasps

Abstract: Males of aculeate Hymenoptera differ in the behavioural adaptations employed to locate and secure mates. The ecological and evolutionary bases of these differences are explored in this paper. Male bees and wasps search for females by patrolling widely within emergence-nesting areas or within patches of flowers attractive to conspecific females, or by waiting at landmarks, at specific emergence sites, or at nests. Nest dispersion, flower distribution, the type of female mating system and the nature of male-male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
144
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(151 citation statements)
references
References 83 publications
3
144
0
1
Order By: Relevance
“…Indeed, the learning capacity of honeybee (A. mellifera) drones (Benatar, et al 1995) was shown to be similar to that of workers despite drones, being fed by workers in the colony, are not foraging on flowers. Alcock, et al (1978) pointed out, males of several Apoidea species are attracted by flowers that are also highly attractive to females (including gynes) and visits to particular flowers may enhance their chances to encounter a mate by visiting these flowers. However, with an elaborate and costly pre-mating behaviour in form of patrolling (Alcock, et al 1978;Eickwort and Ginsberg 1980) it is unlikely that flowers are chosen to increase queen encounter rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, the learning capacity of honeybee (A. mellifera) drones (Benatar, et al 1995) was shown to be similar to that of workers despite drones, being fed by workers in the colony, are not foraging on flowers. Alcock, et al (1978) pointed out, males of several Apoidea species are attracted by flowers that are also highly attractive to females (including gynes) and visits to particular flowers may enhance their chances to encounter a mate by visiting these flowers. However, with an elaborate and costly pre-mating behaviour in form of patrolling (Alcock, et al 1978;Eickwort and Ginsberg 1980) it is unlikely that flowers are chosen to increase queen encounter rates.…”
Section: Discussionmentioning
confidence: 99%
“…Males, in contrast, visit flowers only for their own energy demands and typically spend most of the day patrolling (Svensson 1979;Goulson 2003). They preferentially forage early in the morning and late in the afternoon (Svensson 1979;Alcock, et al 1978;Eickwort and Ginsberg 1980), which may result in fewer flower visits per day than for foragers. Nevertheless, a mean of over 10,000 pollen grains per individual male should be sufficient to facilitate pollination in most plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies to date have reported little or no pre-copulatory courtship behavior among bees (eg Batra, 1966;Barrows, 1975;Alcock et al, 1978;Triplett and Gittins, 1988;. Nomia (Epinomia) triangulifera Vachal, reported on here, seems unusual because of its extremely complex pre-copulatory courtship behavior, combined with structural modifications.…”
Section: Introductionmentioning
confidence: 93%